Development of a multi-component intervention to promote participation of Black and Latinx individuals in biomedical research. Issue 1 (14th June 2021) - Danila, Maria I.; Allison, Jeroan J.; Goins, Karin Valentine; Chiriboga, Germán; Fischer, Melissa; Puliafico, Melissa; Mudano, Amy S.; Rahn, Elizabeth J.; Merchant, Jeanne; Lawrence, Colleen E.; Dunkel, Leah; Israel, Tiffany; et al.
Abstract: Introduction: Barriers to research participation by racial and ethnic minority group members are multi-factorial, stem from historical social injustices and occur at participant, research team, and research process levels. The informed consent procedure is a key component of the research process and represents an opportunity to address these barriers. This manuscript describes the development of the Strengthening Translational Research in Diverse Enrollment (STRIDE) intervention, which aims to improve research participation by individuals from underrepresented groups. Methods: We used a community-engaged approach to develop an integrated, culturally, and literacy-sensitive, multi-component intervention that addresses barriers to research participation during the informed consent process. This approach involved having Community Investigators participate in intervention development activities and using community engagement studios and other methods to get feedback from community members on intervention components. Results: The STRIDE intervention has three components: a simulation-based training program directed toward clinical study research assistants that emphasizes cultural competency and communication skills for assisting in the informed consent process, an electronic consent (eConsent) framework designed to improve health-related research material comprehension and relevance, and a "storytelling" intervention in which prior research participants from diverse backgrounds share their experiences delivered via video vignettes during the consent process. Conclusions: The community engaged development approach resulted in a multi-component intervention that addresses known barriers to research participation and can be integrated into the consent process of research studies. Results of an ongoing study will determine its effectiveness at increasing diversity among research participants.